Experimental investigations on active control of multifrequency helicopter vibrations using discrete model predictive sliding mode control. (December 2018) - Ma, Xunjun; Lu, Yang; Wang, Fengjiao
The presented experimental results illustrate the recent advances in the reduction of multifrequency vibrations of helicopter fuselage using an active control of structural response system. Recently, to cancel the multifrequency helicopter vibrations, a hybrid control approach has been proposed combining the filtered-x least mean square algorithm with a discrete model predictive sliding mode controller. To verify its effectiveness and self-adaptability, a set of active control experiments of structural response are conducted on a free–free elastic beam, which simulates a helicopter in flight. Considering that the helicopter vibrations in practical applications are much more complex, the further experiments of real-time active control are performed using a model helicopter test system. Higher discrete frequency components, which are actually of concern, are selected as the control objectives during the tests. The algorithm's control effects are sufficiently checked by single-input single-output and multiple-input multiple-output tests under different excitation conditions. For many cases the attenuation of measured response exceed level of 20 dB, with maximum reduction reaching 34.1 dB. These two sets of tests confirm that the active control system is practical for canceling the multifrequency helicopter vibrations.